International Capital Market Linkages: A Synthesis of Prior Literature (International Journal of Banking and Finance, 2015)
In recent years, financial market integration has become a central theme in international finance literature, due to its important implications for many parties involved. The contribution of research on this topic has been substantial and covered several relevant issues, whether at the micro or macro level. This study presents a detailed review on the literature of capital market integration along with their possible limitations. In addition, a comparison is provided between the different empirical approaches used in investigating the level to which capital markets are integrated. It can be concluded from the literature survey that capital market integration is still a moot point, as the empirical evidence is rather inconclusive. Thus, the potential gains derived from, and limitations of, cross-border diversification are still at the core of the debate; and that perhaps surprisingly this issue is not yet fully resolved.